2002
DOI: 10.1097/00006123-200208000-00033
|View full text |Cite
|
Sign up to set email alerts
|

Shaking Limb Transient Ischemic Attacks: Unusual Presentation of Carotid Artery Occlusive Disease: Report of Two Cases

Abstract: After surgery, the shaking limb episodes ceased for both patients. Postoperative single-photon emission computed tomographic scans for Patient 1 demonstrated increased cerebral blood flow in response to acetazolamide challenge. These data provide support for the concept that shaking limb TIAs are related to hemodynamic failure and that improvements in cerebral blood flow through conducting vessels can alleviate the condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The precise mechanism of the limb movements is unclear, but the hypothesis is that they are caused by transient focal cerebral ischemia attributable to insufficient brain perfusion, resulting from severe atherosclerotic obstructive extracerebral or intracerebral artery disease. [1][2][3][4][5][6] The cystic nodule in the right thyroid lobe led to compression of the sympathical nerves, and to posterior From the *…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The precise mechanism of the limb movements is unclear, but the hypothesis is that they are caused by transient focal cerebral ischemia attributable to insufficient brain perfusion, resulting from severe atherosclerotic obstructive extracerebral or intracerebral artery disease. [1][2][3][4][5][6] The cystic nodule in the right thyroid lobe led to compression of the sympathical nerves, and to posterior From the *…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanism of the limb movements is unclear, but the hypothesis is that they are caused by transient focal cerebral ischemia attributable to insufficient brain perfusion, resulting from severe atherosclerotic obstructive extracerebral or intracerebral artery disease. [1][2][3][4][5][6] The cystic nodule in the right thyroid lobe led to compression of the sympathical nerves, and to posterior displacement of the right carotid artery. After excluding focal cerebral ischemia and metabolic disturbances as causative factor for these focal manifestations, we hypothesize that rotation of the head, displacing the thyroid cystic nodule resulting in carotid artery compression, in combination with orthostatic position change, led to severe cerebral hypoperfusion causing the transient neurologic deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with more common presentations of TIA, the rare phenomenon of limb-shaking typically signifies high-grade stenosis or occlusion of one or more major cerebral arteries [8]. At particular risk are patients who also have orthostatic hypotension [3,7,11], as systemic hypotension can accentuate already impaired cerebral perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of severe carotid occlusive disease, TIAs can rarely cause limb shaking [8,12]: the sudden, involuntary, often brief, jerky movements of the arm or leg or both [8]. Recurrent limb shaking has been described in cases of severe carotid stenosis combined with orthostatic hypotension [3,7,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Limb-shaking TIA has been reported as an unusual type of TIA, most commonly caused by transient cerebral ischemia due to severe stenosis or occlusion of an extracranial internal carotid artery [1][2][3] . Recently, Han et al [4] reported that ACA stenosis can also induce limb-shaking TIA.…”
Section: Discussionmentioning
confidence: 99%